Peran Teknisi Master Control Room (MCR) TV Muhammadiyah (TVMu) Dalam Program Netizen Bertanya Ustadz Menjawab - Ackmal Rafli; R. Hiru Muhammad (Lembaga Pengembangan Kinerja Dosen, 2023)
The master control room (MCR) is called the master because of its function as the main broadcast controller. There is also what is called a sub control, which functions as a studio broadcast control room, both a production studio and a news studio. Morison (2018) argues that the role of the master control room technician has a more position as an operator than a technician because he has to coordinate all the activities and work results of many people. The master control technician is responsible for the appearance of broadcast on air television stations. already happened after ready before broadcast. This study uses descriptive research with a qualitative approach. Data collection techniques using interviews, literature studies, observation, and documentation. Master Control Room (MCR) includes: Character Generator, Audio control, Camera Switcher, Presentation, VTR material room section, master control console section, studio section, and recording section. Broadcast program broadcast by Netizens Asking Ustadz Responding is supported by crews who serve as broadcast references by using a teamwork strategy in carrying out their duties and obligations to produce the highest broadcast quality output and minimize broadcast interruptions.